Narratives of health and illness: Arts-based research capturing the lived experience of dementia. (August 2019) - Moss, Hilary; O'Neill, Desmond
Introduction: This paper presents three artists' residencies in a geriatric medicine unit in a teaching hospital. The aim of the residencies was creation of new work of high artistic quality reflecting the lived experience of the person with dementia and greater understanding of service user experience of living with dementia. This paper also explores arts-based research methodologies in a medical setting. Method: Arts-based research and narrative enquiry were the method used in this study. Artists had extensive access to service users with dementia, family carers and clinical team. Projects were created through collaboration between clinical staff, arts and health director, artist, patients and family carers. Each performance was accompanied by a public seminar discussing dementia. Evaluations were undertaken following each residency. The process of creating artistic responses to dementia is outlined, presented and discussed. Results: The artworks were well received with repeat performances and exhibitions requested. Evaluations of each residency indicated increased understanding of dementia. The narratives within the artworks aided learning about dementia. The results are a new chamber music composition, a series of visual artworks created collaboratively between visual artist and patients and family carers and a dance film inspired by a dancer's residency, all created through narrative enquiry. Discussion and conclusion: These projects support the role of arts-based research as creative process and qualitative research method which contributes to illuminating and exploring the lived experience of dementia. The arts act as a reflective tool for learning and understanding a complex health condition, as well as creating opportunities for increased understanding and public awareness of dementia. Issues arising in arts-based research in medical settings are highlighted, including ethical issues, the importance of service user narrative and multidisciplinary collaboration in arts and health practice and research.